Using the Job Demands-Resources Model to Predict Job Satisfaction of Employees in Indonesia - Amirah Widia Adiarti; Dimyati Dimyati (Journal of Educational, Health and Community Psychology, 2021)
Although the job demands-resources model (JD-R) is getting much attention in the literature, there is limited, if any, empirical research in Indonesia. This study used the JD-R model to predict job satisfaction in Indonesia with a sample of 17,177 employees. Using data from the 5th wave of the Indonesian Family Life Survey, Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) were performed for data analysis. The main findings revealed a positive relationship between job resources and job satisfaction, and a negative relationship between challenging job demands and job satisfaction beyond the contribution of gender, age, education, marital status, and job type. The findings of this study suggest that managers should provide employees with more resources and engage them in crafting behaviors.Keywords: job demands, job resources, job satisfaction, JD-R model, Indonesia